Sublimações do cotidiano: metamorfoses da imagem e do tempo em um trabalho videográfico - Paula, Arlen Costa de (2019)
This dissertation presents reflections about the construction of an artistic work through the digital video technique. It is about a research to explore the poetic sensibility in the video-graphic language domain with the purpose to obtain results of anamorphic nature, through the utilization of the resource called slit scan, which allows image distortion by frame interleaving. The theme around the organization of these reflections is the quotidian of the urban circuit, constituted by roads in the outskirts of the city of Uberlandia, by locomotion vehicles, vegetation and the Brazilian cerrado sky. Regarding the theoretical references to this research, it was constituted of works by authors dedicated to videoarts, such as Arlindo Machado, Philipe Dubois and Michael Rush. Regarding plastic references, these are represented by works of artists who performed similar nature artworks, such as Nam June Paik, Wolf Vostell, Eder Santos, Egbert Mittelstadt, Steina Vasulka and Miska Knapek. Through an edition process which included montage, the repetition of moving images, as well as the work with soundtracks, the artist achieved plastic results which aroused in the spectator sensations of sublimatic nature.